Coronavirus Disease-2019 (COVID-19): An Overview - Saini, Mahendra; Parihar, Nikhita; Soni, Shankar Lal; Sharma, Vandana (Asian Journal of Pharmaceutical Research and Development, 2021)
There is a new public health crises threatening the world with the emergence and unfold of two019 novel coronavirus (2019-nCoV) or the severe acute metabolism syndrome coronavirus two (SARS-CoV-2). COVID-19 is a spread of coronavirus is the family Coronaviridae. The malady is believed to originate from crackers Associate in Nursing was unfold to people through unknown medium in an exceedingly town, China. Severe acute metabolism syndrome coronavirus 2 (SARS- CoV-2) could also be a very transmissible and infective coronavirus that emerged in late 2019 and has caused an outbreak|avirus|a virulent disease|a pestilence} of acute disease, named, ‘coronavirus malady 2019’ (COVID-19), that threatens human health and public safety. throughout this Review, we have a tendency to to tend to explain the essential medicine of SARS- CoV-2, together with genomic characteristics, and receptor use, lightness its key distinction from antecedent acquainted coronaviruses. we have a tendency to to tend to summarize current data of clinical, medicine, and pathological choices of COVID-19, additionally as recent progress in animal models, and antiviral treatment approach for SARS- CoV-2 infection. we have a tendency to to tend to to boot discuss the potential life hosts and disease origin of this rising virus well.